Students’ Translation Strategies in Translating General English Texts - Rosalia, Harnita (Har Press Indonesia, 2025)
This study aims to examine the translation strategies used by fifth-semester EFL students at Universitas Negeri Makassar in translating general English texts into Indonesian. A qualitative descriptive approach was employed, involving the analysis of students’ translated texts and semi-structured interviews with 18 purposively selected participants who had completed a translation course. The findings reveal that literal translation was the most frequently used strategy, followed by modulation, borrowing, reduction, and adaptation, with occasional use of amplification and transposition. While literal translation dominated due to students’ preference for maintaining source-text structure, the use of modulation and borrowing indicates an emerging awareness of meaning, naturalness, and communicative intent. The study also identifies three key factors influencing students’ strategy choices: linguistic proficiency, cultural and contextual awareness, and translator self-confidence. These results suggest that students are in a transitional stage of translation competence, shifting gradually from form-based to meaning-oriented decision-making. Understanding these factors is essential for designing translation instruction that not only teaches strategy use, but also supports reflective awareness and confidence-building in EFL learners.